Study on the Salivary Microbial Alteration of Men With Head and Neck Cancer and Its Relationship With Symptoms in Southwest China - Zuo, Hao-Jiang; Fu, Mei R.; Zhao, Hui-Ling; Du, Xin-Wen; Hu, Zi-Yi; Zhao, Xun-Ying; Ji, Xiao-Qin; Feng, Xian-Qiong; Zhumajiang, Wuerken; Zhou, Ting-Hui; Tian, Ya-Li; Pei, Xiao-Fang; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
This study explored the association between oral microbes and head and neck cancer (HNC) as well as symptoms related to patients with HNC before surgical treatment. Fifty-six patients with HNC and 64 matched healthy controls were recruited from West China hospital in Southwest China. The demographic, clinical, and symptom data were collected. Salivary samples were collected to determine the microbial characteristics using 16S rRNA gene sequencing. Patients with HNC presented increased Capnocytophaga abundances. The oral microbial markers as Capnocytophaga (area under the curve=0.81) achieved a high classification power between the HNC patients and healthy controls. Moreover, using Capnocytophaga in conjunction with symptoms of voice/speech difficulty and pain achieved an overall predicting accuracy of 95% comparing with using Capnocytophaga alone (79.2% accuracy) in distinguishing the HNC patients from healthy controls. Salivary microbial profiles and HNC symptoms may be potential biomarkers for HNC screening.